The yield spread as a predictor for buy or sell signals for sectoral indices of the JSE - Roeber, Christine (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The predictive nature of the yield curve has been of interest to researchers for years. In this thesis, the evidence for the yield curve as a predictor is examine, specifically as a predictor for bear markets in the JSE stock market for 8 sub-sectoral indices. The study explores a dynamic market timing strategy for timing the South African stock market compared to a normal buy-and-hold strategy. First, probit models are estimated for each of the sectoral indices which did not prove to have tracked well all the bear market phases. Then a dynamic market timing portfolio is simulated against a buy-and-hold only strategy, the dynamic market timing portfolio proved to have outperformed a buy-and-hold strategy for almost all the indices. Thus, a Henriksson-Merton parametric model test which tests for market timing ability was done on these sub-indices. The research finds that the yield curve in South Africa is not a useful tool for a buy-sell strategy for most of the sub-sectoral indices of the JSE.
Keywords: Yield curve; Rate of return -- South Africa; Yield spread; Interest rate; Johannesburg Stock Exchange